The cymothoid isopod Anilocra chromis is negatively associated with multiple metrics of host condition in the Caribbean damselfish Chromis multilineata - Jan-Alexis Barry; Kyle G. Jerris; Teresa R. Turner; Jenilee B. Robinson; Matthew D. Nicholson; Paul C. Sikkel (Marine Biology, 2026)
Parasitism is widespread among fishes in nature and can have significant impacts on individuals, populations, and communities. The family Cymothoidae includes over 380 species of parasitic isopods that infect a wide variety of host fishes, mostly in tropical and subtropical oceans. Despite their conspicuous nature, spatiotemporal patterns of infestation and effects on hosts have been studied for only a small percentage of species. The brown chromis ( Chromis multilineata ) is a common planktivorous damselfish associated with reefs in the tropical western Atlantic. Brown chromis are frequently infested with the large cymothoid isopod Anilocra chromis. In this study, we quantified the prevalence of infection among five sites and over two years in the US Virgin Islands (before and after major hurricanes). We further quantified the relationship between Anilocra infection status and the coinfection of other parasites as well as three metrics of potential impact: gonadal development, rate of food intake, and locomotion. Our results show that parasite prevalence differed significantly among sites. Additionally, while there was variation in coinfection with other parasites among sites, there was no relationship between the presence of Anilocra and the abundance of other parasites. There was a significant negative effect of Anilocra infection on male chromis gonads, feeding behavior (as determined by a decrease in bite-rates), and locomotion (as determined by an increase in fin-beats). Overall, these findings suggest that parasitism by Anilocra chromis is negatively associated with multiple metrics of fitness and health in host fishes, and thus likely has consequences at the population level.

Coral-dwelling Caribbean gobies exhibit distinct skin microbiota compared to other sympatric species - Ana Pereira; Raquel Xavier; Anya Brown; Jeanne Bloomberg; Gina C. Hendrick; Matthew D. Nicholson; Mallory Kastner; Marta C. Soares; Amy Apprill; Paul C. Sikkel (Coral Reefs, 2026)
Microbial communities fundamentally shape ecosystem function and biodiversity across all biological systems through complex dynamics. In coral reef ecosystems, understanding the dynamics of these microbial communities has become critical for predicting reef responses to environmental stressors. Fish skin microbiota are highly susceptible to environmental changes and may vary significantly across species and geographic locations, yet the extent to which these variations occur remain poorly understood. Here, we compared the skin microbiota of four closely related and sympatric cryptobenthic gobiid species, that exhibit different behavioral ecologies (cleaning vs.non-cleaning), ecological niches (water column, coral-, or sand-dwelling) and phylogenetic affinities ( Elacatinus vs. Coryphopterus ), yet reside in the same reef patches in St. Croix and Puerto Rico, eastern Caribbean. Coral-dwelling gobies, including cleaning sharknose and non-cleaning peppermint gobies, exhibited significantly lower microbial diversity compared to reef-hovering and sand-dwelling species (both non-cleaning). These coral dwellers showed unique microbial signatures despite having similar alpha diversity levels. Core microbiota analysis also revealed striking differences between coral-dwelling and reef-hovering/sand-dwelling species, with the core microbiome of the former dominated by Vibrio , Pseudoalteromonas , and Alteromonas in the case of cleaning gobies and by Endozoicomonas in the case of peppermint gobies, while reef-hovering and sand-dwelling gobies exhibited diverse core microbiota with greater overlap between species. Ecological niche occupancy and reef habitat selection appear to be primary drivers of skin microbiota composition in gobiid fishes, rather than cleaning behavior and/or host phylogenetic affinities alone, though species-specific skin mucus properties likely also contribute to selective bacterial colonization patterns.

Methoxyacetic acid exposure in rats induces N-butyrylglycinuria consistent with beta-oxidation impairment - Samuele Sala; Janonna Kadyrov; Andres Bernal; Andres M. Castillo; Preechaya Naraprasertkul; Nadia Paesalasakul; Proud Bekanan; Issariya Dhitsuwon; Thanaporn Kulthawatsiri; Reika Masuda; Manthan Sharma; Jutarop Phetcharaburanin; et al. (Archives of Toxicology, 2026)

A GIS-based framework for hybrid offshore wind and floating solar power plants in Australia - Fida Ali; Rodney A. Stewart; Mohammad J. Sanjari; Jennifer A. Hayward; Robert C. Nicholson; Amir Etemad-Shahidi (Ocean & Coastal Management, 2026)

Corrigendum to “Unravelling inulin molecules in food sources using a matrix-assisted laser desorption/ionization magnetic resonance mass spectrometry (MALDI-MRMS) pipeline” [Food Res. Int. 184 (2024) 114276] - Sung-Tong Chin; Berin A. Boughton; Melvin C.L. Gay; Alyce C. Russell; Yimin Wang; Vimalnath Nambiar; Mark P. McHenry; Elaine Holmes; Jeremy K. Nicholson; Ruey Leng Loo (Food Research International, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Identification of evidence gaps and future research needs in food safety - E. Burton; S.P. Borriello; P.J. Gregory; J. Healing; C. Nicholson; T.H. Oliver; S. Pearson; R. Smith; M. Tildesley; J. Wastling; J. O'Brien (Trends in Food Science & Technology, 2026)

Response of epithelial cell lines from the rainbow trout gut and gill to ammonia - Daylan T. Pritchard; Caio J. Nicholson de Figueiroa; Niels C. Bols; Lucy E. J. Lee (In Vitro Cellular & Developmental Biology - Animal, 2026)

Interlaboratory clinical chemistry parameter variation in seven-day acute hydrazine toxicity studies in the Sprague-Dawley rat - Janonna Kadyrov; Samuele Sala; Lucy Grigoroff; Reika Masuda; Samantha Lodge; Timothy M. Ebbels; Michael D. Reily; Donald Robertson; Lois Lehman-McKeeman; John Shockcor; Bruce D. Car; Craig Thomas; et al. (Archives of Toxicology, 2026)
Clinical chemistry retains its position as a cornerstone of toxicological assessment, yet inter-laboratory variability in baseline values remains a challenge for the integration and interpretation of multisite datasets. This study leveraged a publicly available clinical chemistry database to assess the impact of inter-laboratory variability in response to hydrazine-induced steatosis. Seventeen clinical chemistry and physico-chemical parameters were evaluated in response to a single dose of hydrazine (at 30 mg/kg or 90 mg/kg) administered to Sprague-Dawley rats ( n = 83) across five different pharmaceutical companies and compared with sham-dosed control animals. Hydrazine exposure produced a distinct and consistent biochemical signature at 48 h post-dose across the combined sample set from all laboratory sites, characterised by increased serum bilirubin and BUN and decreased serum protein concentrations, alongside atypical reductions in ALT and AST due to transaminase inhibition. Despite sizable inter-laboratory differences in response when considering single assays, multivariate analysis of the complete dataset was able to extract a core pathological response signature. Early changes at 24 h post-dose in AST, ALT, total protein, and calcium demonstrated strong predictive value for 48-h toxicity profiles (AUROC 0.98), underscoring the translational potential of early biomarkers. This study highlights both the robustness and contextual limitations of clinical chemistry data in toxicological studies. It underscores the importance of matched-control designs and multivariate approaches for multisite studies and advocates for the integration of early predictive modelling to optimise study design and align with the principles of the Replace, Reduce, and Refine initiative.

Wild bees mediate fruit quality via seed set in highbush blueberry: A quantitative synthesis - Maxime Eeraerts; Clark Kogan; Rufus Isaacs; Péter Batáry; Brett R. Blaauw; Kyle Bobiwash; Joshua W. Campbell; Pablo Cavigliasso; Jaret C. Daniels; James D. Ellis; Jason Gibbs; Lauren Goldstein; et al. (Agriculture, Ecosystems & Environment, 2025)

Increased quadriceps intermuscular adipose tissue in chronic liver disease is associated with an altered muscle transcriptome compared with healthy age matched controls - J. I. Quinlan; T. Nicholson; C. Bell; A. Dhaliwal; F. R. Williams; S. L. Allen; S. Choudhary; A. V. Rowlands; A. M. Elsharkawy; M. J. Armstrong; C. A. Greig; J. M. Lord; et al. (GeroScience, 2025)
Muscle fat infiltration (i.e., myosteatosis) is an important index of muscle health and pathology in disease states, such as chronic liver disease (CLD). However, it is unknown whether myosteatosis differs due to anatomical location. Further, the mechanistic implications of divergent intermuscular adipose tissue (IMAT) deposition remain unknown in patients with CLD. Thirty-three patients with CLD (55.0 ± 10.5 years) and 17 healthy controls (HC) (49.6 ± 15.4 years) were recruited. Quadriceps IMAT was estimated between 20 and 80% of muscle length and psoas IMAT at L3 via MRI. Body composition, muscle strength, and habitual activity were assessed. Fasted vastus lateralis muscle biopsies were collected and subjected to RNA sequencing analysis. ClinicalTrials.gov identifier: NCT04734496. IMAT was greater in CLD compared with HC in both quadriceps and psoas ( P < 0.0001). Quadriceps IMAT positively correlated with BMI ( r = 0.62), body fat ( r = 0.65), age ( r = 0.36), and negatively correlated with maximal knee extensor strength ( r = −0.45) and habitual physical activity ( r = −0.50) in CLD and HC. One hundred sixty-nine differentially expressed genes (DEGs) were identified in low IMAT CLD vs. HC, and 178 DEGs were identified in high IMAT CLD vs. HC. CLD patients with high and low IMAT exhibited defined expression profiles, with only 39 DEGs (representing 12.7%) in common. Pathway analysis of DEGs revealed enrichment of atrophic and pro-inflammatory pathways in the high IMAT group. IMAT is greater in patients with CLD compared to HC, irrespective of anatomical location, and is associated with reductions in muscle function and may be exacerbated by physical inactivity. IMAT appears to alter the muscle transcriptome in COLD, potentially exacerbating muscle loss. Graphical Abstract

Exposure and health risks of benzene from combustion by gas stoves: A modelling approach in U.S. homes - Anchal Garg; Yannai Kashtan; Metta Nicholson; Colin J. Finnegan; Eric D. Lebel; Drew R. Michanowicz; Seth B.C. Shonkoff; Kari C. Nadeau; Robert B. Jackson (Journal of Hazardous Materials, 2025)

A clinical chemical atlas of xenobiotic toxicity for the Sprague–Dawley rat - Janonna Kadyrov; Samuele Sala; Lucy Grigoroff; Novia Minaee; Reika Masuda; Samantha Lodge; Timothy M. Ebbels; Michael D. Reily; Donald Robertson; Lois Lehman-McKeeman; John Shockcor; Bruce D. Car; et al. (Archives of Toxicology, 2025)
The Consortium for Metabonomic Toxicology (COMET) studies was designed to model metabolic responses to organ- and mechanism-specific toxins to predict acute drug toxicity in rats. A range of clinical chemical parameters were measured in 7-day toxicology studies for 86 toxins eliciting a range of organ- and mechanism-specific effects. Additionally, 21 surgical or physiological stressors were evaluated to identify physiological or metabolic responses that might confound the interpretation of observed toxicity profiles. From these studies on a total of 3473 rats measured at six pharmaceutical companies, we provide a set of 12 serum and 5 urine physical and clinical chemistry parameters. Samples were collected at 24 h, 48 h and 168 h post-dose for each animal and are presented as a downloadable database file. We also summarise the main observations based on the group response at the level of the individual toxin. We demonstrate that correlations between parameters, such as serum bilirubin and aspartate aminotransferase (AST), provide a more nuanced profile of organ-specific toxicity than consideration of individual parameters alone. In addition, we highlight the variability in the measured parameters across the dataset attributable to inter-laboratory differences, and the heterogeneity of metabolic responses to particular compounds or differences in temporal patterns of response. This clinical chemistry atlas of toxicity serves as a valuable reference tool for evaluating the potential toxicity of novel drug candidates.

The impact of measuring conditions on the relationship between sensory and measured juiciness in plant-based burgers - Raisa E.D. Rudge; Felix Briner; Reed A. Nicholson; Colleen Cottrell; Janet Collins; Louwrens C. Hoffman; Jason R. Stokes; Heather E. Smyth (Food Hydrocolloids, 2025)

Evaluation of tissue-specific extraction protocols for comprehensive lipid profiling - Dana Hicks; Monique J. Ryan; Amira Allahham; Lucy W. Barrett; Silvia Lee; Benjamin Bartlett; Herbert Ludewick; Natalie C. Ward; Ruey Leng Loo; Girish Dwivedi; Jeremy K. Nicholson; Julien Wist; et al. (Analytica Chimica Acta, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Pollination Across the Diel Cycle: A Global Meta‐Analysis - Liam Kendall; Charlie C. Nicholson (Ecology Letters, 2025)
The daily transition between day and night, known as the diel cycle, is characterised by significant shifts in environmental conditions and biological activity, both of which can affect crucial ecosystem functions like pollination. Despite over six decades of research into whether pollination varies between day and night, consensus remains elusive. We compiled the evidence of diel pollination from 135 studies with pollinator exclusion experiments involving 139 angiosperms. We used phylogenetic multi‐level meta‐analysis to test the influence of environmental conditions and plant functional traits on diel pollination differences. Our synthesis revealed an overall lack of difference in pollination between day and night; many plant species (90% of studied spp.) exhibit similar pollination success across the diel cycle. Diel pollination differences were partially explained by elevation: nocturnal pollination success was greater at low elevations, whereas diurnal pollination was more beneficial at higher elevations. Furthermore, floral traits related to pollinator attraction (odour, colour) and anthesis time influenced diel pollination differences. In the light of increasing anthropogenic pressures on biodiversity, as well as unique challenges for nocturnal biota, this synthesis underscores the diel complementarity of pollinators for many flowering plants and the importance of considering both nocturnal and diurnal pollinators in agricultural and conservation contexts.

Helium, carbon and nitrogen isotope evidence for slab influence on volcanic gas emissions at Rabaul caldera, Papua New Guinea - B.T. McCormick Kilbride; P.H. Barry; T.P. Fischer; G. Holland; M. Hudak; S. Nowicki; C. Ballentine; M.D. Fox; M. Höhn; I. Itikarai; M.D. Johnson; K. Mulina; et al. (Chemical Geology, 2024)

Pollination deficits and their relation with insect pollinator visitation are cultivar-dependent in an entomophilous crop - Maxime Eeraerts; Stan Chabert; Lisa W. DeVetter; Péter Batáry; John J. Ternest; Kris Verheyen; Kyle Bobiwash; Kayla Brouwer; Daniel García; G. Arjen de Groot; Jason Gibbs; Lauren Goldstein; et al. (Agriculture, Ecosystems & Environment, 2024)

Unravelling inulin molecules in food sources using a matrix-assisted laser desorption/ionization magnetic resonance mass spectrometry (MALDI-MRMS) pipeline - Sung-Tong Chin; Berin A. Boughton; Melvin C.L. Gay; Alyce C. Russell; Yimin Wang; Vimalnath Nambiar; Mark P. McHenry; Elaine Holmes; Jeremy K. Nicholson; Ruey Leng Loo (Food Research International, 2024)

Functional diversity among coral reef fishes as consumers of ectoparasites - Matthew D. Nicholson; J. Andrés Pagán; Gina C. Hendrick; Paul C. Sikkel (Coral Reefs, 2024)

Using the system of environmental-economic accounting ecosystem accounting for policy: A case study on forest ecosystems - S. King; R. Agra; A. Zolyomi; H. Keith; E. Nicholson; X. de Lamo; R. Portela; C. Obst; M. Alam; M. Honzák; R. Valbuena; P.A.L.D. Nunes; et al. (Environmental Science & Policy, 2024)

Carbonate budgets induced by coral restoration of a Great Barrier Reef site following cyclone damage - C. Isabel Nuñez Lendo; David J. Suggett; Chloë Boote; Alicia McArdle; Freda Nicholson; Eric E. Fisher; David Smith; Emma F. Camp (Frontiers in Marine Science, 2024)
Coral carbonate production is fundamental to reef accretion and, consequently, the preservation of essential reef ecosystem services, such as wave attenuation and sustained reef biodiversity. However, the unprecedented loss of coral reefs from anthropogenic impacts has put these valuable ecosystem services at risk. To counteract this loss, active rehabilitation of degraded reef sites has accelerated globally. A variety of restoration practices exist, tailored to local site needs and reef types. For sites where there is a significant unconsolidated substrate, Mars Assisted Reef Restoration System (MARRS, or “Reef Stars”) has been utilised to contribute toward rubble stabilisation and reef accretion. However, the effect of the Reef Stars on the local carbonate budgets and structural complexity has not been assessed. For that purpose, we assess coral cover and reef complexity through a census-based approach to identify the contribution of carbonate producers and eroders alongside studying coral skeletal properties to estimate current carbonate budgets on a rehabilitated site compared to natural unrehabilitated reef and rubble patches on the mid-Great Barrier Reef. Our research identified positive ecological processes and ecological functions such as increased carbonate budget, coral cover and structural complexity at the restored site compared to the non-intervened reef and rubble patches. In general, no impacts on skeletal rigour relative to this active reef restoration were found for two key coral species and the Acropora rubble for most of the skeletal traits. However, Pocillopora damicornis hardness seemed to decrease on the restored site compared to the other sites, demonstrating different performances of coral species during restoration activities that should be considered to maximise return-on-effort of restoration activities. Overall, our data demonstrate that consideration of carbonate budgets is important for measuring success of coral restoration initiatives and that coral restoration can be a relevant tool to recover lost local carbonate budgets.

A spatially explicit model of landscape pesticide exposure to bees: Development, exploration, and evaluation - Eric V. Lonsdorf; Maj Rundlöf; Charlie C. Nicholson; Neal M. Williams (Science of The Total Environment, 2024)

Blood meal identification reveals extremely broad host range and host-bias in a temporary ectoparasite of coral reef fishes - Gina C. Hendrick; Matthew D. Nicholson; J. Andres Pagan; John M. Artim; Maureen C. Dolan; Paul C. Sikkel (Oecologia, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Mapping connectivity and conservation opportunity on agricultural lands across the conterminous United States - Justin P. Suraci; Caitlin E. Littlefield; Charlie C. Nicholson; Mitchell C. Hunter; Ann Sorensen; Brett G. Dickson (Biological Conservation, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Detecting forest response to droughts with global observations of vegetation water content - Alexandra G. Konings; Sassan S. Saatchi; Christian Frankenberg; Michael Keller; Victor Leshyk; William R. L. Anderegg; Vincent Humphrey; Ashley M. Matheny; Anna Trugman; Lawren Sack; Elizabeth Agee; Mallory L. Barnes; et al. (Global Change Biology, 2021)
Droughts in a warming climate have become more common and more extreme, making understanding forest responses to water stress increasingly pressing. Analysis of water stress in trees has long focused on water potential in xylem and leaves, which influences stomatal closure and water flow through the soil‐plant‐atmosphere continuum. At the same time, changes of vegetation water content (VWC) are linked to a range of tree responses, including fluxes of water and carbon, mortality, flammability, and more. Unlike water potential, which requires demanding in situ measurements, VWC can be retrieved from remote sensing measurements, particularly at microwave frequencies using radar and radiometry. Here, we highlight key frontiers through which VWC has the potential to significantly increase our understanding of forest responses to water stress. To validate remote sensing observations of VWC at landscape scale and to better relate them to data assimilation model parameters, we introduce an ecosystem‐scale analog of the pressure–volume curve, the non‐linear relationship between average leaf or branch water potential and water content commonly used in plant hydraulics. The sources of variability in these ecosystem‐scale pressure‐volume curves and their relationship to forest response to water stress are discussed. We further show to what extent diel, seasonal, and decadal dynamics of VWC reflect variations in different processes relating the tree response to water stress. VWC can also be used for inferring belowground conditions—which are difficult to impossible to observe directly. Lastly, we discuss how a dedicated geostationary spaceborne observational system for VWC, when combined with existing datasets, can capture diel and seasonal water dynamics to advance the science and applications of global forest vulnerability to future droughts.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Finding Oxford’s medieval Jewry using organic residue analysis, faunal records and historical documents - J. Dunne; E. Biddulph; P. Manix; T. Gillard; H. Whelton; S. Teague; C. Champness; L. G. Broderick; R. Nicholson; P. Blinkhorn; E. Craig-Atkins; B. Jervis; et al. (Archaeological and Anthropological Sciences, 2021)
Food is often one of the most distinctive expressions of social, religious, cultural or ethnic groups. However, the archaeological identification of specific religious dietary practices, including the Jewish tradition of keeping kosher , associated with ritual food practices and taboos, is very rare. This is arguably one of the oldest known diets across the world and, for an observant Jew, maintaining dietary laws (known as Kashruth) is a fundamental part of everyday life. Recent excavations in the early medieval Oxford Jewish quarter yielded a remarkable assemblage of animal bones, marked by a complete absence of pig specimens and a dominance of kosher (permitted) birds, domestic fowl and goose. To our knowledge, this is the first identification of a Jewish dietary signature in British zooarchaeology, which contrasted markedly with the previous Saxon phase where pig bones were present in quantity and bird bones were barely seen. Lipid residue analysis of pottery from St Aldates showed that vessels from the possible Jewish houses were solely used to process ruminant carcass products, with an avoidance of pig product processing, correlating well with the faunal data. In contrast, lipid analysis of pottery from comparative assemblages from the previous Saxon phase at the site and a contemporaneous site in the city, The Queen’s College, shows that the majority of these vessels appear to have been used to process mixtures of both ruminant and non-ruminant (pig) products. Here, the combination of organic residue analysis, site excavation and animal and fish bone evidence was consistent with the presence of Jewish houses in eleventh- and twelfth-century St Aldates, Oxford, hitherto only suspected through documentary information. This is the first identification of specific religious dietary practices using lipid residue analysis, verifying that, at least 800 years ago, medieval Jewish Oxford communities practised dietary laws known as Kashruth.

The effects of environment and ontogeny on the skin microbiome of two Stegastes damselfishes (Pomacentridae) from the eastern Caribbean Sea - Raquel Xavier; Ana Pereira; Andres Pagan; Gina C. Hendrick; Matthew D. Nicholson; Daniela Rosado; Marta C. Soares; Marcos Pérez-Losada; Paul C. Sikkel (Marine Biology, 2020)

Natural hazard threats to pollinators and pollination - Charlie C. Nicholson; Paul A. Egan (Global Change Biology, 2020)
Natural hazards are naturally occurring physical events that can impact human welfare both directly and indirectly, via shocks to ecosystems and the services they provide. Animal‐mediated pollination is critical for sustaining agricultural economies and biodiversity, yet stands to lose both from present exposure to natural hazards, and future climate‐driven shifts in their distribution, frequency, and intensity. In contrast to the depth of knowledge available for anthropogenic‐related threats, our understanding of how naturally occurring extreme events impact pollinators and pollination has not yet been synthesized. We performed a systematic review and meta‐analysis to examine the potential impacts of natural hazards on pollinators and pollination in natural and cultivated systems. From a total of 117 studies (74% of which were observational), we found evidence of community and population‐level impacts to plants and pollinators from seven hazard types, including climatological (extreme heat, fire, drought), hydrological (flooding), meteorological (hurricanes), and geophysical (volcanic activity, tsunamis). Plant and pollinator response depended on the type of natural hazard and level of biological organization observed; 19% of cases reported no significant impact, whereas the majority of hazards held consistent negative impacts. However, the effects of fire were mixed, but taxa specific; meta‐analysis revealed that bee abundance and species richness tended to increase in response to fire, differing significantly from the mainly negative response of Lepidoptera. Building from this synthesis, we highlight important future directions for pollination‐focused natural hazard research, including the need to: (a) advance climate change research beyond static “mean‐level” changes by better incorporating “shock” events; (b) identify impacts at higher levels of organization, including ecological networks and co‐evolutionary history; and (c) address the notable gap in crop pollination services research—particularly in developing regions of the world. We conclude by discussing implications for safeguarding pollination services in the face of global climate change.

Mismatched outcomes for biodiversity and ecosystem services: testing the responses of crop pollinators and wild bee biodiversity to habitat enhancement - Charlie C. Nicholson; Kimiora L. Ward; Neal M. Williams; Rufus Isaacs; Keith S. Mason; Julianna K. Wilson; Julia Brokaw; Larry J. Gut; Nikki L. Rothwell; Thomas J. Wood; Sujaya Rao; George D. Hoffman; et al. (Ecology Letters, 2020)
Supporting ecosystem services and conserving biodiversity may be compatible goals, but there is concern that service‐focused interventions mostly benefit a few common species. We use a spatially replicated, multiyear experiment in four agricultural settings to test if enhancing habitat adjacent to crops increases wild bee diversity and abundance on and off crops. We found that enhanced field edges harbored more taxonomically and functionally abundant, diverse, and compositionally different bee communities compared to control edges. Enhancements did not increase the abundance or diversity of bees visiting crops, indicating that the supply of pollination services was unchanged following enhancement. We find that actions to promote crop pollination improve multiple dimensions of biodiversity, underscoring their conservation value, but these benefits may not be spilling over to crops. More work is needed to identify the conditions that promote effective co‐management of biodiversity and ecosystem services.

JC virus infection of meningeal and choroid plexus cells in patients with progressive multifocal leukoencephalopathy - Sarah M. Corbridge; Richard C. Rice; Linda A. Bean; Christian Wüthrich; Xin Dang; Daniel A. Nicholson; Igor J. Koralnik (Journal of NeuroVirology, 2019)

Simultaneous‐count models to estimate abundance from counts of unmarked individuals with imperfect detection - Gerard Edward Ryan; Emily Nicholson; Jonathan C. Eames; Thomas N. E. Gray; Robin Loveridge; Simon P. Mahood; Phearun Sum; Michael A. McCarthy (Conservation Biology, 2019)
We developed a method to estimate population abundance from simultaneous counts of unmarked individuals over multiple sites. We considered that at each sampling occasion, individuals in a population could be detected at 1 of the survey sites or remain undetected and used either multinomial or binomial simultaneous‐count models to estimate abundance, the latter being equivalent to an N‐mixture model with one site. We tested model performance with simulations over a range of detection probabilities, population sizes, growth rates, number of years, sampling occasions, and sites. We then applied our method to 3 critically endangered vulture species in Cambodia to demonstrate the real‐world applicability of the model and to provide the first abundance estimates for these species in Cambodia. Our new approach works best when existing methods are expected to perform poorly (i.e., few sites and large variation in abundance among sites) and if individuals may move among sites between sampling occasions. The approach performed better when there were >8 sampling occasions and net probability of detection was high (>0.5). We believe our approach will be useful in particular for simultaneous surveys at aggregation sites, such as roosts. The method complements existing approaches for estimating abundance of unmarked individuals and is the first method designed specifically for simultaneous counts.

Farm Water Program: Using the Water Savings Calculator - C. Norman; C. Walters; M. McFarlane; C. Nicholson; D. Lawler (Irrigation and Drainage, 2019)
Calculating the water savings expected to be realised from improvements to farm irrigation systems is an integral part of the Farm Water Program being delivered in northern Victoria, Australia. Water savings form the basis of works packages landowners undertake to improve water productivity of their irrigation systems. Through the Farm Water Program, landowners agree to transfer more than half of the water savings for environmental purposes in exchange for funding to do works. The Farm Water Program originated in 2009 following the introduction of an AU$300 million On‐Farm Irrigation Efficiency Program by the Australian government. The Goulburn Broken and North Central Catchment Management authorities, relevant Victoria government agencies and irrigation industry bodies formed a consortium to bid for funding to be used on properties across the Goulburn Murray Irrigation District of Victoria. The organisations have worked in partnership as the Farm Water Program and have successfully delivered 620 projects involving over 80 000 megalitres of water savings. The water savings calculator was developed using research findings conducted in the region and has been widely accepted and confirmed by landowners as they have developed projects. This paper describes the processes of using the water savings calculator to determine project water savings. Copyright © 2018 John Wiley & Sons, Ltd.

C-reactive protein concentration and risk of selected obesity-related cancers in the Women’s Health Initiative - Theodore M. Brasky; Geoffrey C. Kabat; Gloria Y. F. Ho; Cynthia A. Thomson; Wanda K. Nicholson; Wendy E. Barrington; Marisa A. Bittoni; Sylvia Wassertheil-Smoller; Thomas E. Rohan (Cancer Causes & Control, 2018)

Revisiting the taxonomy of the genus Elizabethkingia using whole-genome sequencing, optical mapping, and MALDI-TOF, along with proposal of three novel Elizabethkingia species: Elizabethkingia bruuniana sp. nov., Elizabethkingia ursingii sp. nov., and Elizabethkingia occulta sp. nov. - Ainsley C. Nicholson; Christopher A. Gulvik; Anne M. Whitney; Ben W. Humrighouse; James Graziano; Brian Emery; Melissa Bell; Vladimir Loparev; Phalasy Juieng; Jarrett Gartin; Chantal Bizet; Dominique Clermont; et al. (Antonie van Leeuwenhoek, 2018)

Detection of Tilapia Lake Virus in Egyptian fish farms experiencing high mortalities in 2015 - P Nicholson; M A Fathi; A Fischer; C Mohan; E Schieck; N Mishra; A Heinimann; J Frey; B Wieland; J Jores (Journal of Fish Diseases, 2017)

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

The eyespot resistance genes Pch1 and Pch2 of wheat are not homoeoloci - M. Pasquariello; J. Ham; C. Burt; J. Jahier; S. Paillard; C. Uauy; P. Nicholson (Theoretical and Applied Genetics, 2017)

Pilot Trial of Intravenous Lipid Emulsion Treatment for Severe Nifedipine-Induced Shock - Christine M. Murphy; Cliff Williams; Michael E. Quinn; Brian Nicholson; Thomas Shoe; Michael C. Beuhler; William P. Kerns (Journal of Medical Toxicology, 2016)

Justice is the goal: divestment as climate change resistance - Eve Bratman; Kate Brunette; Deirdre C. Shelly; Simon Nicholson (Journal of Environmental Studies and Sciences, 2016)

Mapping a Type 1 FHB resistance on chromosome 4AS of Triticum macha and deployment in combination with two Type 2 resistances - C. Burt; A. Steed; N. Gosman; M. Lemmens; N. Bird; R. Ramirez-Gonzalez; S. Holdgate; P. Nicholson (Theoretical and Applied Genetics, 2015)

Development of a Control Strategy for Benzene Impurity in HPMCAS-Stabilized Spray-Dried Dispersion Drug Products Using a Science-Based and Risk-Based Approach - Hongfei Yue; Sarah J. Nicholson; Joel D. Young; Daniel Hsieh; Rodney J. Ketner; Robert G. Hall; Jeremy Sackett; Elizabeth C. Banks; John A. Castoro; Michael E. Randazzo (Pharmaceutical Research, 2015)

“Modeling the impact of natural resource-based poverty traps on food security in Kenya: The Crops, Livestock and Soils in Smallholder Economic Systems (CLASSES) model” - Emma C. Stephens; Charles F. Nicholson; Douglas R. Brown; David Parsons; Christopher B. Barrett; Johannes Lehmann; David Mbugua; Solomon Ngoze; Alice N. Pell; Susan J. Riha (Food Security, 2012)

Modelling experimental uveitis: barrier effects in autoimmune disease - David Nicholson; Emma C. Kerr; Owen G. Jepps; Lindsay B. Nicholson (Inflammation Research, 2012)

Changing patterns of carbon allocation in lake phytoplankton: an FTIR analysis - Andrew P. Dean; James M. Nicholson; David C. Sigee (Hydrobiologia, 2012)

Exploiting co-linearity among grass species to map the Aegilops ventricosa-derived Pch1 eyespot resistance in wheat and establish its relationship to Pch2 - C. Burt; P. Nicholson (Theoretical and Applied Genetics, 2011)

Identification of a QTL conferring seedling and adult plant resistance to eyespot on chromosome 5A of Cappelle Desprez - C. Burt; T. W. Hollins; P. Nicholson (Theoretical and Applied Genetics, 2011)

Carbon-13 (13C) Labeling of Bacillus subtilis Vegetative Cells and Spores: Suitability for DNA Stable Isotope Probing (DNA-SIP) of Spores in Soils - Wayne L. Nicholson; Jeffrey Fedenko; Andrew C. Schuerger (Current Microbiology, 2009)

The dddP gene, encoding a novel enzyme that converts dimethylsulfoniopropionate into dimethyl sulfide, is widespread in ocean metagenomes and marine bacteria and also occurs in some Ascomycete fungi - J. D. Todd; A. R. J. Curson; C. L. Dupont; P. Nicholson; A. W. B. Johnston (Environmental Microbiology, 2009)
Summary The marine alphaproteobacterium Roseovarius nubinhibens ISM can produce the gas dimethyl sulfide (DMS) from dimethylsulfoniopropionate (DMSP), a widespread secondary metabolite that occurs in many phytoplankton. Roseovarius possesses a novel gene, termed dddP , which when cloned, confers on Escherichia coli the ability to produce DMS. The DddP polypeptide is in the large family of M24 metallopeptidases and is wholly different from two other enzymes, DddD and DddL, which were previously shown to generate DMS from dimethylsulfoniopropionate. Close homologues of DddP occur in other alphaproteobacteria and more surprisingly, in some Ascomycete fungi. These were the biotechnologically important Aspergillus oryzae and the plant pathogen, Fusarium graminearum . The dddP gene is abundant in the bacterial metagenomic sequences in the Global Ocean Sampling Expedition. Thus, dddP has several novel features and is widely dispersed, both taxonomically and geographically.

The dddP gene, encoding a novel enzyme that converts dimethylsulfoniopropionate into dimethyl sulfide, is widespread in ocean metagenomes and marine bacteria and also occurs in some Ascomycete fungi - J. D. Todd; A. R. J. Curson; C. L. Dupont; P. Nicholson; A. W. B. Johnston (Environmental Microbiology, 2009)

Net community production in the deep euphotic zone of the subtropical North Pacific gyre from glider surveys - David Nicholson; Steven Emerson; Charles C. Eriksen (Limnology and Oceanography, 2008)
Seagliders, deployed through most of 2005 in the subtropical North Pacific gyre, made measurements of temperature, salinity, and dissolved oxygen to quantify net community production (NCP) at Station A Long‐ Term Oligotrophic Habitat Assessment (ALOHA) of the Hawaii Ocean Time‐series (HOT) using an oxygen mass balance approach. A ‘bowtie’‐shaped pattern, 50 km by 50 km in size was repeatedly traversed at two week intervals with the goal of observing the influence of Rossby waves and eddies on the productivity of the study region. Rossby waves and eddies in the region cause a vertical displacement of isopycnal depth of ~±50 m at the base of the euphotic zone. Shoaling of isopycnals is demonstrated to drive productivity in the deep euphotic zone. Four mesoscale shoaling events were observed between February and November in 2005. During each event when isopycnals shoaled, oxygen concentrations on isopycnals increased, fluorescence in the deep euphotic zone was higher, and net community production was elevated. Productivity in the deep euphotic zone was strongly influenced by Rossby waves and eddies, but this influence was not observed to extend into the mixed layer.

The development of PCR-based markers for the selection of eyespot resistance genes Pch1 and Pch2 - N. H. Chapman; C. Burt; H. Dong; P. Nicholson (Theoretical and Applied Genetics, 2008)

A novel locus for distal motor neuron degeneration maps to chromosome 7q34-q36 - Sumana Gopinath; Ian P. Blair; Marina L. Kennerson; Jennifer C. Durnall; Garth A. Nicholson (Human Genetics, 2007)

Hepatotoxin-induced hypertyrosinemia and its toxicological significance - T. Andrew Clayton; John C. Lindon; Jeremy R. Everett; Claude Charuel; Gilles Hanton; Jean-Loic Le Net; Jean-Pierre Provost; Jeremy K. Nicholson (Archives of Toxicology, 2007)

Metabonomics Techniques and Applications to Pharmaceutical Research & Development - John C. Lindon; Elaine Holmes; Jeremy K. Nicholson (Pharmaceutical Research, 2006)

Evaluating Supplemental Mass Pollination Efficacy in a Lodgepole Pine Orchard in British Columbia using Chloroplast DNA Markers - Michael Stoehr; Helga Mehl; George Nicholson; Greg Pieper; C. Newton (New Forests, 2006)

Environmental Metabonomics: Applying Combination Biomarker Analysis in Earthworms at a Metal Contaminated Site - Jacob G. Bundy; David J. Spurgeon; Claus Svendsen; Peter K. Hankard; Jason M. Weeks; Daniel Osborn; John C. Lindon; Jeremy K. Nicholson (Ecotoxicology, 2004)

Hepatotoxin-induced hypercreatinaemia and hypercreatinuria: their relationship to one another, to liver damage and to weakened nutritional status - T. Andrew Clayton; John C. Lindon; Jeremy R. Everett; Claude Charuel; Gilles Hanton; Jean-Loic Le Net; Jean-Pierre Provost; Jeremy K. Nicholson (Archives of Toxicology, 2004)

An hypothesis for a mechanism underlying hepatotoxin-induced hypercreatinuria - T. Andrew Clayton; John C. Lindon; Jeremy R. Everett; Claude Charuel; Gilles Hanton; Jean-Loic Le Net; Jean-Pierre Provost; Jeremy K. Nicholson (Archives of Toxicology, 2003)

Comparison of changes in toxicity during growth of Anabaena circinalis (cyanobacteria) determined by mouse neuroblastoma bioassay and HPLC - Vincent Testé; Jean-François Briand; Brenton C. Nicholson; Simone Puiseux-Dao (Journal of Applied Phycology, 2002)

Neurofibromatosis pseudogene amplification underlies euchromatic cytogenetic duplications and triplications of proximal 15q - J. C. K. Barber; I. E. Cross; Fiona Douglas; James C. Nicholson; Kirk J. Moore; Caroline E. Browne (Human Genetics, 1998)

Micropropagation of Spathoglottis plicata - W.-L. Teng; L. Nicholson; M.-C. Teng (Plant Cell Reports, 1997)

Nestling obesity in procellariiform seabirds: temporal and stochastic variation in provisioning and growth of short-tailed shearwaters Puffinus tenuirostris - K. C. Hamer; L. W. Nicholson; J. K. Hill; R. D. Wooller; J. S. Bradley (Oecologia, 1997)

The effect of phosphate on the transformation of ferrihydrite into crystalline products in alkaline media - C. R. Paige; W. J. Snodgrass; Ronald V. Nicholson; J. M. Scharer; Q. H. He (Water, Air, & Soil Pollution, 1997)

the effect of phosphate on the transformation of ferrihydrite into crystalline products in alkaline media - C. R. Paige; W. J. Snodgrass; Ronald V. Nicholson; J. M. Scharer; Q. H. He (Water, Air, & Soil Pollution, 1997)

Investigations of decayed sandstone colonised by a species ofTrentepohlia - Rachael D. Wakefield; Melanie S. Jones; M. Jeff Wilson; Maureen E. Young; Keith Nicholson; Dennis C. M. Urquhart (Aerobiologia, 1996)

Studies on the comparative toxicity of S-(1,2-dichlorovinyl)-L-cysteine, S-(1,2-dichlorovinyl)-L-homocysteine and 1,1,2-trichloro-3,3,3-trifluoro-1-propene in the Fischer 344 rat - Maria L. Anthony; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Studies of the biochemical toxicology of uranyl nitratein the rat - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Studies of the biochemical toxicology of uranyl nitrate in the rat - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Studies on the effects ofl(αS,5S)-α-amino-3-chloro-4,5-dihydro-5-isoxazoleacetic acid (AT-125) on 4-aminophenol-induced nephrotoxicity in the Fischer 344 rat - Maria L. Anthony; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1993)

Cephaloridine-induced nephrotoxicity in the Fischer 344 rat: proton NMR spectroscopic studies of urine and plasma in relation to conventional clinical chemical and histopathological assessments of nephronal damage - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1992)

Proton NMR spectroscopic studies on the metabolism and biochemical effects of hydrazine in vivo - S. M. Sanins; J. A. Timbrell; C. Elcombe; J. K. Nicholson (Archives of Toxicology, 1992)

Deformities in chironomid larvae as indicators of pollution (pesticide) stress - C. P. Madden; P. J. Suter; B. C. Nicholson; A. D. Austin (Aquatic Ecology, 1992)

Effects of biliary cannulation and buthionine sulphoximine pretreatment on the nephrotoxicity of para-aminophenol in the Fischer 344 rat - K. P. R. Gartland; C. T. Eason; F. W. Bonner; J. K. Nicholson (Archives of Toxicology, 1990)